Intersecting inequalities and the Sustainable Development Goals: Insights from Brazil - Naila Kabeer; Ricardo Goul\~ao Santos (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Concerns about the dramatic rise in income inequality across the world and, at the same time, assessments of national progress on the Millennium Development Goals made it clear that it is the intersection of income inequality, marginalized social identities and, very often, locational disadvantage which leads to the systematic exclusion of certain groups. In recognition of this, the Sustainable Development Goals now include a commitment to the reduction of income and other inequalities. Our paper uses national data from Brazil between 2002 and 2013 to examine retrospectively how it has performed on some of the indicators relating to the inclusive principles articulated by the SDGs. Our paper examines the extent to which this decline in income inequality was accompanied by a decline in intersecting inequalities and explores some of the economic, political and social explanations given for the country's performance.
Keywords: D63; I24; O15; O19; 330; income distribution; intersecting inequalities; labour market segmentation; sustainable development goals; Brazil